Association of circulating leptin and adiponectin levels with colorectal cancer risk: A systematic review and meta-analysis of case-control studies. (August 2021) - Wang, Yan; Li, Junyong; Fu, Xiaolin; Li, Jialing; Liu, Lihua; Alkohlani, Albatoul; Tan, Shing Cheng; Low, Teck Yew; Hou, Yue
Highlights: The overall analysis found that circulating levels of leptin and adiponectin were not significantly associated with CRC risk. Subgroup analysis revealed that a higher level of adiponectin was associated with an increased CRC risk among overweight individuals. Subgroup analysis revealed that a higher level of adiponectin was associated with a decreased CRC risk among normal weight individuals. Abstract: Purpose: Leptin and adiponectin are adipokines which have been commonly implicated in carcinogenesis. As such, many studies have investigated the association of circulating leptin and adiponectin levels with colorectal cancer (CRC) risk. However, the results remained inconsistent. Methods: In this work, we performed a systematic review and meta-analysis to precisely examine the association between circulating levels of leptin and adiponectin and CRC risk. A systematic literature search was performed in PubMed/MEDLINE, Scopus, Web of Science, and EMBASE databases from inception until October 2020. The pooled effect size was then estimated by calculating the odds ratio (OR). Results: A total of 23 records (comprising 26 studies) were included in the meta-analysis. The overall analysis found that circulating levels of leptin and adiponectin were not significantly associated with CRC risk (P > 0.05). Interestingly, subgroup analysis revealed that a higher level of adiponectin was significantly associated with an increased CRC risk among overweight individuals (OR = 1.16; 95 % CI: 1.02, 1.32), and a decreased CRC risk among normal weight individuals (OR = 0.76; 95 % CI: 0.62, 0.92). Besides, a higher level of adiponectin was also significantly associated with a decreased risk of CRC in men (OR = 0.76; 95 % CI: 0.59, 0.98). Conclusions: In conclusion, circulating leptin level was not associated with CRC risk, but that of adiponectin was associated with CRC risk only in specific subgroups.